Carbon Fluxes of Contrasting Degraded Peatland Pilot Sites During Early-stage Restoration: Ex-milled Bare Peat and Grazed Grassland Conversion - Anna T. Keightley; Christopher D. Field; Michael Longden; Simon J. M. Caporn (Environmental Management, 2026)
The recovery of degraded peatlands can make significant contributions to reducing greenhouse gas emissions and climate warming. This study examines restoration techniques on shallow ex-milled peatland and intensively grazed pasture on deeper peat, both subject to prior drainage. Carbon greenhouse gases (GHGs) were monitored for 3 years following restoration treatment. After drainage-blocking measures, the ex-milled peatland was ‘companion planted’ with Eriophorum species and Sphagnum . The carbon balance was highly dependent on plant age and condition, with a high CO 2 equivalent (CO 2 e) uptake when plants were vigorously growing (year 1: −22.4 ± 32.9 t CO 2 e ha −1 yr −1 ), and high emission when plants were mature and in various stages of senescence (year 2: 26.1 ± 26.4 and year 3: 16.4 ± 9.7 t CO 2 e ha −1 yr −1 ). Bare peat controls had a mean emission of 6.21 ± 1.68 t CO 2 e ha −1 yr −1 over the study period. At the other site, the grazed pasture was stripped, the bare surface planted with Sphagnum plugs, and irrigation was intensively managed via bunding, ditches, and automatic water pumping. Carbon GHG emissions were significantly reduced on this ‘carbon farm’ (2.77 ± 0.95 t CO 2 e ha −1 yr −1 ) compared to a neighbouring drained, grazed pasture control (31.7 ± 10.3 t CO 2 e ha −1 yr −1 ) over the study period (mean ± SD throughout). It appears clear that the cyclical nature of Eriophorum plant growth may only deliver carbon benefits on shallow peat over the long term if groundwater levels can be adequately supported and if climatic conditions are favourable. Conversion of grazed pasture to wetter farming crops, such as Sphagnum , can potentially deliver immediate carbon benefits, although, in this pilot, any potential loss of CO 2 e due to degraded topsoil removal, creation of bunds and irrigation ditches was not accounted for.

Conservation genomics of the imperiled Leon springs pupfish, Cyprinodon bovinus, across temporal and spatial scales - Robert J. Bretzing-Tungate; Kevin W. Conway; Megan G. Bean; Ryan K. Smith; Christopher M. Hollenbeck; Andrew T. Fields; Elizabeth P. Dolan; Steven M. Mussmann; David S. Portnoy (Conservation Genetics, 2026)
The Leon Springs pupfish, Cyprinodon bovinus , is federally listed as endangered and currently confined to spring-fed pools on the Diamond Y Spring Preserve in Pecos County, Texas, USA. A refuge population is maintained by U.S. Fish and Wildlife Service in Dexter, New Mexico, USA because of ongoing threats from hybridization with the introduced congener, the sheepshead minnow, C. variegatus. To inform continued conservation and management planning for this species, a comprehensive conservation genomics study using double digest restriction-site associated DNA sequencing was performed. No evidence of contemporary hybridization or recent introgression between C. bovinus and C. variegatus was found. The refuge population was significantly differentiated from wild samples collected at two locations, and the two wild populations (less than 1 km apart) also exhibited significant heterogeneity in allele frequencies. Estimates of within population diversity were smaller for wild locations than the refuge population. Correspondingly, the wild populations’ contemporary effective population size estimates were smaller than the refuge’s effective population size estimates (145–262 versus 679). Temporal analyses, involving genetic data collected from samples obtained in 2013, suggest an increased magnitude of drift acting on the wild populations relative to the reserve population. Based on the results of this study, it appears that steps taken in the early 2000s to eradicate genetically admixed individuals from the wild populations were successful. However, habitat fragmentation and small effective population sizes of the wild populations have led to accelerated drift and decreasing levels of within population genetic diversity. This may jeopardize the long-term persistence of C. bovinus .

Comparing the spatial effects and longevity of key fuel treatments in California using spaceborne lidar data - Mengyu Liang; Christopher Hakkenberg; Lydia Marie Villa; Laura Duncanson; Christopher B. Field (Journal of Environmental Management, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Which Plant Traits Increase Soil Carbon Sequestration? Empirical Evidence From a Long‐Term Poplar Genetic Diversity Trial - John L. Field; Brandon P. Sloan; Matthew E. Craig; Parker Calloway; Sarah L. Ottinger; Thomas Mead; Rose Z. Abramoff; Mirko Pavicic Venegas; Hari B. Chhetri; Kathy Haiby; Udaya C. Kalluri; Wellington Muchero; et al. (Global Change Biology, 2025)
Plants play a key role in mediating soil response to global change, and breeding or engineering crops to increase soil organic carbon (SOC) storage is a potential route to land‐based carbon dioxide removal in agricultural systems. However, due to limited observational datasets plus shifting paradigms of SOC stabilization, it is unclear which plant traits are most important for enhancing different types of soil organic matter. Existing long‐term common gardens of genetically diverse plant populations may provide an opportunity to evaluate biological controls on SOC, separate from environmental or management variability. Here we report on soil and root chemical data collected for 24 genotypes within a 13‐year‐old common garden in northwestern Oregon planted with a large natural variant population of Populus trichocarpa . Fractionating surface soil (0–15 cm) revealed substantial variation in stocks of mineral‐associated organic matter (MAOM; 18–67 t C/ha) and particulate organic matter (POM; 2–22 t C/ha). Tree genotype explained 24% and 26% of the MAOM and POM stock variability, respectively, after controlling for background variability. We found minimal association between SOC concentration and either aboveground tree productivity or root biomass recalcitrance (C/N ratios and lignin content). In contrast, root elemental content appeared influential for MAOM‐C concentration, which showed a strong positive association with root aluminum (Al) and a strong negative association with root boron (B) and magnesium (Mg). Furthermore, root concentrations of these elements were highly heritable (57%–78%) and not simply a reflection of background variation in soil elemental concentrations. We estimate that surface SOC stocks under these 24 genotypes have diverged at rates of up to 1.2–4.3 t C/ha/year. These results suggest that long‐term genetic diversity trials have value for elucidating biological controls on soil organic matter dynamics, and that traits associated with root elemental content may be a useful target for enhancing biosequestration.

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Taphonomic damage obfuscates interpretation of the retroarticular region of the Asteriornis mandible - Abi Crane; Juan Benito; Albert Chen; Grace Musser; Christopher R. Torres; Julia A. Clarke; Stephan Lautenschlager; Daniel T. Ksepka; Daniel J. Field (Geobios, 2025)

Spatiotemporal changes of atmospheric depositions over 43 years in south-central Ontario - Huaxia Yao; Joelle Young; April James; David Lembcke; Christopher McConnell; Tim Field; Lance Aspden; Sara Rawski; Chris Jones; Michelle Palmer; Claire Holeton; James A. Rusak; et al. (Atmospheric Environment, 2025)

Deep-time history of primate behavior and ecology as revealed by ancestral state reconstructions - Jeffrey K. Spear; Eva A. Hoffman; Juri A. Miyamae; Christopher D. Whalen; Alyssa M. Arre; Chloe Chen-Kraus; Margaret K. Corley; Matteo Fabbri; Jacques A. Gauthier; Michael Hanson; Amanda Leiss; Nicolás Mongiardino Koch; et al. (Journal of Mammalian Evolution, 2025)

Towards environmental justice: A framework and strategic approach for implementing community based participatory research in the earth and environmental sciences - Alexis M. Wilson; Emily Polk; Christopher B. Field; Scott Fendorf (Environmental Science & Policy, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Assessment of genomic diversity within and between two cryptic shiners, the West Texas shiner ( Notropis megalops ) and the Texas shiner ( Notropis amabilis ) - Kayla R. Dye; Andrew T. Fields; Megan G. Bean; Sarah M. Robertson; Christopher M. Hollenbeck; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2025)
The presence of cryptic species can hinder effective conservation planning and implementation, as has been the case for speciose groups of freshwater fishes that are difficult to differentiate due to conserved morphologies. The West Texas shiner Notropis megalops and the Texas shiner Notropis amabilis are a cryptic pair of leuciscids (minnows) that co‐occur in spring‐fed tributaries of the Rio Grande in Texas and Mexico. Both N. megalops and N. amabilis are listed as Species of Greatest Conservation Need by the Texas Parks and Wildlife Department. Notropis amabilis is widespread and listed as apparently secure by Texas Parks and Wildlife Department whereas N. megalops has a very limited distribution and has not been ranked by Texas Parks and Wildlife Department because of data deficiency. Morphological differences between these species have been described; however, proper identification in situ remains problematic. Furthermore, given their range of overlap there is potential for hybridization, and limited genetic data have been collected comparing the species. Therefore, reduced representation genomic and mitochondrial sequencing data were used to reassess the distinctness of the species, screen for hybridization, and characterize their relative frequencies throughout their range of overlap. Genomic analyses recovered two distinct genetic groups corresponding to the species ( F' CT = 0.89) with no evidence of admixture or introgression. The species were found to co‐occur at three sampling locations, two in the Devils River and one in the Pecos, but not in equal frequencies. Overall, these results provide data and tools for further research on N. megalops needed for accurate conservation policies and management practices.

One size does not fit all: Intra– and interspecific variation of den site use in two marsupial glider species in fragmented forest - Christopher M. McLean; Jed Field; Samuel A.R. Hayley; Matthew Hingee; Chad T. Beranek (Forest Ecology and Management, 2025)

Biochar-Sulfate Reducing Bacteria synergy: A green approach for antimony removal and recovery from high-concentrated waters - Marina M. Atilano-Camino; Ana P. Canizales Laborín; Angelita M. Ortega Juárez; M. Rosario Sánchez-Macías; Iván Moreno-Andrade; Reyes Sierra-Álvarez; Jim Field; Christopher Rensing; Julián Carrillo-Reyes; Francisco J. Cervantes; Aurora M. Pat-Espadas (Journal of Environmental Chemical Engineering, 2024)

Long‐term elevated precipitation induces grassland soil carbon loss via microbe‐plant–soil interplay - Mengmeng Wang; Xin Sun; Baichuan Cao; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Qun Gao; Jessica L. M. Gutknecht; Xue Guo; Genhe He; Bruce A. Hungate; Jiesi Lei; et al. (Global Change Biology, 2023)
Global climate models predict that the frequency and intensity of precipitation events will increase in many regions across the world. However, the biosphere‐climate feedback to elevated precipitation (eP) remains elusive. Here, we report a study on one of the longest field experiments assessing the effects of eP, alone or in combination with other climate change drivers such as elevated CO 2 (eCO 2 ), warming and nitrogen deposition. Soil total carbon (C) decreased after a decade of eP treatment, while plant root production decreased after 2 years. To explain this asynchrony, we found that the relative abundances of fungal genes associated with chitin and protein degradation increased and were positively correlated with bacteriophage genes, suggesting a potential viral shunt in C degradation. In addition, eP increased the relative abundances of microbial stress tolerance genes, which are essential for coping with environmental stressors. Microbial responses to eP were phylogenetically conserved. The effects of eP on soil total C, root production, and microbes were interactively affected by eCO 2 . Collectively, we demonstrate that long‐term eP induces soil C loss, owing to changes in microbial community composition, functional traits, root production, and soil moisture. Our study unveils an important, previously unknown biosphere‐climate feedback in Mediterranean‐type water‐limited ecosystems, namely how eP induces soil C loss via microbe‐plant–soil interplay.

Spatial and temporal variability of per- and polyfluoroalkyl substances (PFAS) in environmental media of a small pond: Toward an improved understanding of PFAS bioaccumulation in fish - Abbi S. Brown; Xiaoyan Yun; Erica R. McKenzie; Christopher G. Heron; Jennifer A. Field; Christopher J. Salice (Science of The Total Environment, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Sequence of introduction determines the success of contrasting root symbionts and their host - Christopher A. Bell; Emily Magkourilou; Katie J. Field; P.E. Urwin (Applied Soil Ecology, 2023)

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Mercury exposure of tidal marsh songbirds in the northeastern United States and its association with nest survival - Katharine J. Ruskin; Garth Herring; Collin A. Eagles-Smith; Alyssa B. Eiklor; Chris S. Elphick; Matthew A. Etterson; Christopher R. Field; Rebecca A. Longenecker; Adrienne I. Kovach; W. Gregory Shriver; Jennifer Walsh; Brian J. Olsen (Ecotoxicology, 2022)

The limiting factors and regulatory processes that control the environmental responses of C3, C3–C4 intermediate, and C4 photosynthesis - Jennifer E. Johnson; Christopher B. Field; Joseph A. Berry (Oecologia, 2021)
Here, we describe a model of C 3 , C 3 –C 4 intermediate, and C 4 photosynthesis that is designed to facilitate quantitative analysis of physiological measurements. The model relates the factors limiting electron transport and carbon metabolism, the regulatory processes that coordinate these metabolic domains, and the responses to light, carbon dioxide, and temperature. It has three unique features. First, mechanistic expressions describe how the cytochrome b 6 f complex controls electron transport in mesophyll and bundle sheath chloroplasts. Second, the coupling between the mesophyll and bundle sheath expressions represents how feedback regulation of Cyt b 6 f coordinates electron transport and carbon metabolism. Third, the temperature sensitivity of Cyt b 6 f is differentiated from that of the coupling between NADPH, Fd, and ATP production. Using this model, we present simulations demonstrating that the light dependence of the carbon dioxide compensation point in C 3 –C 4 leaves can be explained by co-occurrence of light saturation in the mesophyll and light limitation in the bundle sheath. We also present inversions demonstrating that population-level variation in the carbon dioxide compensation point in a Type I C 3 –C 4 plant, Flaveria chloraefolia , can be explained by variable allocation of photosynthetic capacity to the bundle sheath. These results suggest that Type I C 3 –C 4 intermediate plants adjust pigment and protein distributions to optimize the glycine shuttle under different light and temperature regimes, and that the malate and aspartate shuttles may have originally functioned to smooth out the energy supply and demand associated with the glycine shuttle. This model has a wide range of potential applications to physiological, ecological, and evolutionary questions.

Under the radar: genetic assessment of Rio Grande Shiner (Notropis jemezanus) and Speckled Chub (Macrhybopsis aestivalis), two Rio Grande basin endemic cyprinids that have experienced recent range contractions - Megan J. Osborne; David S. Portnoy; Andrew T. Fields; Megan G. Bean; Christopher W. Hoagstrom; Kevin W. Conway (Conservation Genetics, 2021)

High uncertainty over the future of tidal marsh birds under current sea-level rise projections - Brian T. Klingbeil; Jonathan B. Cohen; Maureen D. Correll; Christopher R. Field; Thomas P. Hodgman; Adrienne I. Kovach; Erika E. Lentz; Brian J. Olsen; W. Gregory Shriver; Whitney A. Wiest; Chris S. Elphick (Biodiversity and Conservation, 2021)

Fire affects the taxonomic and functional composition of soil microbial communities, with cascading effects on grassland ecosystem functioning - Sihang Yang; Qiaoshu Zheng; Yunfeng Yang; Mengting Yuan; Xingyu Ma; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Jessica L. M. Gutknecht; Bruce A. Hungate; Audrey Niboyet; Xavier Le Roux; et al. (Global Change Biology, 2020)
Fire is a crucial event regulating the structure and functioning of many ecosystems. Yet few studies have focused on how fire affects taxonomic and functional diversities of soil microbial communities, along with changes in plant communities and soil carbon (C) and nitrogen (N) dynamics. Here, we analyze these effects in a grassland ecosystem 9 months after an experimental fire at the Jasper Ridge Global Change Experiment site in California, USA. Fire altered soil microbial communities considerably, with community assembly process analysis showing that environmental selection pressure was higher in burned sites. However, a small subset of highly connected taxa was able to withstand the disturbance. In addition, fire decreased the relative abundances of most functional genes associated with C degradation and N cycling, implicating a slowdown of microbial processes linked to soil C and N dynamics. In contrast, fire stimulated above‐ and belowground plant growth, likely enhancing plant–microbe competition for soil inorganic N, which was reduced by a factor of about 2. To synthesize those findings, we performed structural equation modeling, which showed that plants but not microbial communities were responsible for significantly higher soil respiration rates in burned sites. Together, our results demonstrate that fire ‘reboots’ the grassland ecosystem by differentially regulating plant and soil microbial communities, leading to significant changes in soil C and N dynamics.

The future of bioenergy - Walter V. Reid; Mariam K. Ali; Christopher B. Field (Global Change Biology, 2020)
Energy from biomass plays a large and growing role in the global energy system. Energy from biomass can make significant contributions to reducing carbon emissions, especially from difficult‐to‐decarbonize sectors like aviation, heavy transport, and manufacturing. But land‐intensive bioenergy often entails substantial carbon emissions from land‐use change as well as production, harvesting, and transportation. In addition, land‐intensive bioenergy scales only with the utilization of vast amounts of land, a resource that is fundamentally limited in supply. Because of the land constraint, the intrinsically low yields of energy per unit of land area, and rapid technological progress in competing technologies, land intensive bioenergy makes the most sense as a transitional element of the global energy mix, playing an important role over the next few decades and then fading, probably after mid‐century. Managing an effective trajectory for land‐intensive bioenergy will require an unusual mix of policies and incentives that encourage appropriate utilization in the short term but minimize lock‐in in the longer term.

Framework for quantifying population responses to disturbance reveals that coastal birds are highly resilient to hurricanes - Christopher R. Field; Katharine J. Ruskin; Jonathan B. Cohen; Thomas P. Hodgman; Adrienne I. Kovach; Brian J. Olsen; W. Gregory Shriver; Chris S. Elphick (Ecology Letters, 2019)
Changes in the frequency and severity of extreme weather may introduce new threats to species that are already under stress from gradual habitat loss and climate change. We provide a probabilistic framework that quantifies potential threats by applying concepts from ecological resilience to single populations. Our approach uses computation to compare disturbance–impacted projections to a population's normal range of variation, quantifying the full range of potential impacts. We illustrate this framework with projection models for coastal birds, which are commonly depicted as vulnerable to disturbances, especially hurricanes and oil spills. We found that populations of coastal specialists are resilient to extreme disturbances, with high resistance to the effects of short‐term reductions in vital rates and recovery within 20 years. Applying the general framework presented here across disturbance‐prone species and ecosystems would improve understanding of population resilience and generate specific projections of resilience that are needed for effective conservation planning.

Terrestrial gross primary production: Using NIR V to scale from site to globe - Grayson Badgley; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2019)
Terrestrial photosynthesis is the largest and one of the most uncertain fluxes in the global carbon cycle. We find that near‐infrared reflectance of vegetation (NIR V ), a remotely sensed measure of canopy structure, accurately predicts photosynthesis at FLUXNET validation sites at monthly to annual timescales ( R 2 = 0.68), without the need for difficult to acquire information about environmental factors that constrain photosynthesis at short timescales. Scaling the relationship between gross primary production (GPP) and NIR V from FLUXNET eddy covariance sites, we estimate global annual terrestrial photosynthesis to be 147 Pg C/year (95% credible interval 131–163 Pg C/year), which falls between bottom‐up GPP estimates and the top‐down global constraint on GPP from oxygen isotopes. NIR V ‐derived estimates of GPP are systematically higher than existing bottom‐up estimates, especially throughout the midlatitudes. Progress in improving estimated GPP from NIR V can come from improved cloud screening in satellite data and increased resolution of vegetation characteristics, especially details about plant photosynthetic pathway.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Effect of torpor on host transcriptomic responses to a fungal pathogen in hibernating bats - Kenneth A. Field; Brent J. Sewall; Jenni M. Prokkola; Gregory G. Turner; Marianne F. Gagnon; Thomas M. Lilley; J. Paul White; Joseph S. Johnson; Christopher L. Hauer; DeeAnn M. Reeder (Molecular Ecology, 2018)
Hibernation, the use of prolonged torpor to depress metabolism, is employed by mammals to conserve resources during extended periods of extreme temperatures and/or resource limitation. Mammalian hibernators arouse to euthermy periodically during torpor for reasons that are not well understood, and these arousals may facilitate immune processes. To determine whether arousals enable host responses to pathogens, we used dual RNA ‐Seq and a paired sampling approach to examine gene expression in a hibernating bat, the little brown myotis ( Myotis lucifugus ). During torpor, transcript levels differed in only a few genes between uninfected wing tissue and adjacent tissue infected with Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome. Within 70–80 min after emergence from torpor, large changes in gene expression were observed due to local infection, particularly in genes involved in pro‐inflammatory host responses to fungal pathogens, but also in many genes involved in immune responses and metabolism. These results support the hypothesis that torpor is a period of relative immune dormancy and arousals allow for local immune responses in infected tissues during hibernation. Host–pathogen interactions were also found to regulate gene expression in the pathogen differently depending on the torpor state of the host. Hibernating species must balance the benefits of energy and water conservation achieved during torpor with the costs of decreased immune competence. Interbout arousals allow hibernators to optimize these, and other, trade‐offs during prolonged hibernation by enabling host responses to pathogens within brief, periodic episodes of euthermy.

Managing cropland and rangeland for climate mitigation: an expert elicitation on soil carbon in California - Charlotte Y. Stanton; Katharine J. Mach; Peter A. Turner; Seth J. Lalonde; Daniel L. Sanchez; Christopher B. Field (Climatic Change, 2018)

Experimental fire increases soil carbon dioxide efflux in a grassland long‐term multifactor global change experiment - Aaron L. Strong; Tera P. Johnson; Nona R. Chiariello; Christopher B. Field (Global Change Biology, 2017)
Numerous studies have demonstrated that soil respiration rates increase under experimental warming, although the long‐term, multiyear dynamics of this feedback are not well constrained. Less is known about the effects of single, punctuated events in combination with other longer‐duration anthropogenic influences on the dynamics of soil carbon (C) loss. In 2012 and 2013, we assessed the effects of decadal‐scale anthropogenic global change – warming, increased nitrogen (N) deposition, elevated carbon dioxide ( CO 2 ), and increased precipitation – on soil respiration rates in an annual‐dominated Mediterranean grassland. We also investigated how controlled fire and an artificial wet‐up event, in combination with exposure to the longer‐duration anthropogenic global change factors, influenced the dynamics of C cycling in this system. Decade‐duration surface soil warming (1–2 °C) had no effect on soil respiration rates, while +N addition and elevated CO 2 concentrations increased growing‐season soil CO 2 efflux rates by increasing annual aboveground net primary production ( NPP ) and belowground fine root production, respectively. Low‐intensity experimental fire significantly elevated soil CO 2 efflux rates in the next growing season. Based on mixed‐effects modeling and structural equation modeling, low‐intensity fire increased growing‐season soil respiration rates through a combination of three mechanisms: large increases in soil temperature (3–5 °C), significant increases in fine root production, and elevated aboveground NPP . Our study shows that in ecosystems where soil respiration has acclimated to moderate warming, further increases in soil temperature can stimulate greater soil CO 2 efflux. We also demonstrate that punctuated short‐duration events such as fire can influence soil C dynamics with implications for both the parameterization of earth system models ( ESM s) and the implementation of climate change mitigation policies that involve land‐sector C accounting.

High‐resolution tide projections reveal extinction threshold in response to sea‐level rise - Christopher R. Field; Trina S. Bayard; Carina Gjerdrum; Jason M. Hill; Susan Meiman; Chris S. Elphick (Global Change Biology, 2017)
Sea‐level rise will affect coastal species worldwide, but models that aim to predict these effects are typically based on simple measures of sea level that do not capture its inherent complexity, especially variation over timescales shorter than 1 year. Coastal species might be most affected, however, by floods that exceed a critical threshold. The frequency and duration of such floods may be more important to population dynamics than mean measures of sea level. In particular, the potential for changes in the frequency and duration of flooding events to result in nonlinear population responses or biological thresholds merits further research, but may require that models incorporate greater resolution in sea level than is typically used. We created population simulations for a threatened songbird, the saltmarsh sparrow ( Ammodramus caudacutus ), in a region where sea level is predictable with high accuracy and precision. We show that incorporating the timing of semidiurnal high tide events throughout the breeding season, including how this timing is affected by mean sea‐level rise, predicts a reproductive threshold that is likely to cause a rapid demographic shift. This shift is likely to threaten the persistence of saltmarsh sparrows beyond 2060 and could cause extinction as soon as 2035. Neither extinction date nor the population trajectory was sensitive to the emissions scenarios underlying sea‐level projections, as most of the population decline occurred before scenarios diverge. Our results suggest that the variation and complexity of climate‐driven variables could be important for understanding the potential responses of coastal species to sea‐level rise, especially for species that rely on coastal areas for reproduction.

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

Consequences of a warming climate for social organisation in sweat bees - Roger Schürch; Christopher Accleton; Jeremy Field (Behavioral Ecology and Sociobiology, 2016)

Particle Filters to Estimate Properties of Confined Aquifers - Graeme Field; German Tavrisov; Christopher Brown; Alan Harris; O. Patrick Kreidl (Water Resources Management, 2016)

Understanding and responding to danger from climate change: the role of key risks in the IPCC AR5 - Katharine J. Mach; Michael D. Mastrandrea; T. Eren Bilir; Christopher B. Field (Climatic Change, 2016)

Building a sustained climate assessment process - James L. Buizer; Kirstin Dow; Mary E. Black; Katharine L. Jacobs; Anne Waple; Richard H. Moss; Susanne Moser; Amy Luers; David I. Gustafson; T.C. Richmond; Sharon L. Hays; Christopher B. Field (Climatic Change, 2016)

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

On the Response of pH to Inorganic Nutrient Enrichment in Well-Mixed Coastal Marine Waters - Scott W. Nixon; Autumn J. Oczkowski; Michael E. Q. Pilson; Lindsey Fields; Candace A. Oviatt; Christopher W. Hunt (Estuaries and Coasts, 2015)

Testing for a change in diet using fatty acid signatures - Connie Stewart; Sara Iverson; Christopher Field (Environmental and Ecological Statistics, 2014)

Orientation behavior of predaceous ground beetle species in response to volatile emissions identified from yellow starthistle damaged by an invasive slug - Marina Oster; Lincoln Smith; John J. Beck; Abigail Howard; Christopher B. Field (Arthropod-Plant Interactions, 2014)

Heather Moorland Vegetation and Air Pollution: A Comparison and Synthesis of Three National Gradient Studies - Richard J. Payne; Simon J. M. Caporn; Christopher D. Field; Jacky A. Carroll; Jill L. Edmondson; Andrea Britton; Nancy B. Dise (Water, Air, & Soil Pollution, 2014)

Ripping Improves Tree Survival and Growth on Unused Reclaimed Mined Lands - Christopher W. Fields-Johnson; James A. Burger; Daniel M. Evans; Carl E. Zipper (Environmental Management, 2014)

Loss of whole-tree hydraulic conductance during severe drought and multi-year forest die-off - William R. L. Anderegg; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Oecologia, 2014)

Drought's legacy: multiyear hydraulic deterioration underlies widespread aspen forest die‐off and portends increased future risk - William R. L. Anderegg; Lenka Plavcová; Leander D. L. Anderegg; Uwe G. Hacke; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2013)
Forest mortality constitutes a major uncertainty in projections of climate impacts on terrestrial ecosystems and carbon‐cycle feedbacks. Recent drought‐induced, widespread forest die‐offs highlight that climate change could accelerate forest mortality with its diverse and potentially severe consequences for the global carbon cycle, ecosystem services, and biodiversity. How trees die during drought over multiple years remains largely unknown and precludes mechanistic modeling and prediction of forest die‐off with climate change. Here, we examine the physiological basis of a recent multiyear widespread die‐off of trembling aspen ( P opulus tremuloides ) across much of western N orth A merica. Using observations from both native trees while they are dying and a rainfall exclusion experiment on mature trees, we measure hydraulic performance over multiple seasons and years and assess pathways of accumulated hydraulic damage. We test whether accumulated hydraulic damage can predict the probability of tree survival over 2 years. We find that hydraulic damage persisted and increased in dying trees over multiple years and exhibited few signs of repair. This accumulated hydraulic deterioration is largely mediated by increased vulnerability to cavitation, a process known as cavitation fatigue. Furthermore, this hydraulic damage predicts the probability of interyear stem mortality. Contrary to the expectation that surviving trees have weathered severe drought, the hydraulic deterioration demonstrated here reveals that surviving regions of these forests are actually more vulnerable to future droughts due to accumulated xylem damage. As the most widespread tree species in N orth A merica, increasing vulnerability to drought in these forests has important ramifications for ecosystem stability, biodiversity, and ecosystem carbon balance. Our results provide a foundation for incorporating accumulated drought impacts into climate–vegetation models. Finally, our findings highlight the critical role of drought stress accumulation and repair of stress‐induced damage for avoiding plant mortality, presenting a dynamic and contingent framework for drought impacts on forest ecosystems.

Microbial communities and their responses to simulated global change fluctuate greatly over multiple years - Jessica L. M. Gutknecht; Christopher B. Field; Teri C. Balser (Global Change Biology, 2012)
We used microbial lipid analysis to analyze microbial biomass and community structure during 6 years of experimental treatment at the J asper R idge G lobal C hange E xperiment ( JRGCE ), a long‐term multi‐factor global change experiment in a C alifornia annual grassland. The microbial community fingerprint and specific biomarkers varied substantially from year to year, in both control and experimental treatment plots. Possible drivers of the variability included plant growth, soil moisture, and ambient temperature. Surprisingly, background variation in the microbial community was of a larger magnitude than even very significant treatment effects, and this variation appeared to constrain responses to treatment. Microbial communities were mostly not responsive or not consistently responsive to the experimental treatments. Both arbuscular mycorrhizal fungi biomarker abundance (16 : 1 ω5c) and the fungal to bacterial ratio were lower under nitrogen addition in most years. Bacterial lipid biomarker abundances (15 : 0 iso and 16 : 1 ω7c) were higher under nitrogen addition in 2002, the year of largest microbial biomass, suggesting that bacteria could respond more to nitrogen addition in years of better growth conditions. Nitrogen addition and warming led to an interactive effect on the G ram‐positive bacterial biomarker and the fungal to bacterial ratio. These patterns indicate that in C alifornia grassland ecosystems, microbial communities may not respond substantially to future changes in climate and that nitrogen deposition may be a determinant of the soil response to global change. Further, year‐to‐year variation in microbial growth or community composition may be important determinants of ecosystem response to global change.

Climate extremes in California agriculture - David B. Lobell; Angela Torney; Christopher B. Field (Climatic Change, 2011)

California perennial crops in a changing climate - David B. Lobell; Christopher B. Field (Climatic Change, 2011)

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 2. An Evaluation of the Predictive Ability of Effects-Based Sediment-Quality Guidelines - Donald D. MacDonald; Christopher G. Ingersoll; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Ning Wang; Corrine Severn; Ron Gouguet; John Meyer; Jay Field (Archives of Environmental Contamination and Toxicology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Gametophyte life-history dominance of Chondrus crispus (Gigartinaceae, Rhodophyta) along the Atlantic coast of Nova Scotia, Canada - Jack L. Mclachlan; Wade Blanchard; Christopher Field; Nancy I. Lewis (Algae, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Can crop albedo be increased through the modification of leaf trichomes, and could this cool regional climate? - Christopher E. Doughty; Christopher B. Field; Andrew M. S. McMillan (Climatic Change, 2011)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Accentuation of phosphorus limitation in Geranium dissectum by nitrogen: an ecological genomics study - SUSAN SUMMERS THAYER; SAMUEL B. ST CLAIR; CHRISTOPHER B. FIELD; SHAUNA C. SOMERVILLE (Global Change Biology, 2008)
Global climate change experiments have shown changes in productivity, phenology, species composition, and nutrient acquisition and availability; yet, the underlying mechanisms for these responses, especially in multi‐factorial experiments, are poorly understood. Altered nutrient availability is a major consequence of global change, directly due to anthropogenic nitrogen (N) deposition, and indirectly due to shifts in temperature and water availability. In the Jasper Ridge Global Change Experiment, microarrays were used to investigate the transcriptional responses of the dominant dicot, Geranium dissectum , to simulated N deposition. The transcript levels for several photosynthetic genes were elevated in plants exposed to elevated N, as has been reported previously, validating the use of microarrays under field conditions. A coordinated response of a suite of genes previously reported to be induced in response to phosphate (Pi) deficiency was observed, including genes for the glycolytic bypass pathway, which reduces ATP and Pi requirements for sugar degradation, suggesting that the plants were phosphorus (P) limited. Confirming this conclusion, foliar P levels in G. dissectum leaves were reduced to levels that are suboptimal for growth in plants grown in elevated N and elevated CO 2 plots. Thus, although plants commonly produce more biomass in response to elevated N in native grasslands, this growth response may be suboptimal due to a P limitation. Foliar P levels in plants from elevated CO 2 plots were also suboptimal for growth. However, genes indicative of Pi deficiency were not significantly expressed at higher levels. Transcript levels for genes involved in nitrate uptake and assimilation were unchanged by the elevated N deposition treatment, possibly due to the combined impacts of elevated N deposition and P limitation under field conditions. These observations highlight the complexity of the impact of global climate change factors in the field.

Litter Decomposition in a California Annual Grassland: Interactions Between Photodegradation and Litter Layer Thickness - Hugh A. L. Henry; Kathleen Brizgys; Christopher B. Field (Ecosystems, 2008)

Estimation of the CO 2 fertilization effect using growth rate anomalies of CO 2 and crop yields since 1961 - DAVID B. LOBELL; CHRISTOPHER B. FIELD (Global Change Biology, 2008)

Estimation of the carbon dioxide (CO 2 ) fertilization effect using growth rate anomalies of CO 2 and crop yields since 1961 - DAVID B. LOBELL; CHRISTOPHER B. FIELD (Global Change Biology, 2008)
The effect of elevated carbon dioxide (CO 2 ) on crop yields is one of the most uncertain and influential parameters in models used to assess climate change impacts and adaptations. A primary reason for this uncertainty is the limited availability of experimental data on CO 2 responses for crops grown under typical field conditions. However, because of historical variations in CO 2 , each year farmers throughout the world perform uncontrolled yield ‘experiments’ under different levels of CO 2 . In this study, measurements of atmospheric CO 2 growth rates and crop yields for individual countries since 1961 were compared to empirically determine the average effect of a 1 ppm increase of CO 2 on yields of rice, wheat, and maize. Because the gradual increase in CO 2 is highly correlated with major changes in technology, management, and other yield controlling factors, we focused on first differences of CO 2 and yield time series. Estimates of CO 2 responses obtained from this approach were highly uncertain, reflecting the relatively small importance of year‐to‐year CO 2 changes for yield variability. Combining estimates from the top 20 countries for each crop resulted in estimates with substantially less uncertainty than from any individual country. The results indicate that while current datasets cannot reliably constrain estimates beyond previous experimental studies, an empirical approach supported by large amounts of data may provide a potentially valuable and independent assessment of this critical model parameter. For example, analysis of reliable yield records from hundreds of individual, independent locations (as opposed to national scale yield records with poorly defined errors) may result in empirical estimates with useful levels of uncertainty to complement estimates from experimental studies.

Simulated global changes alter phosphorus demand in annual grassland - DUNCAN N. L. MENGE; CHRISTOPHER B. FIELD (Global Change Biology, 2007)
In the Jasper Ridge Global Change Experiment – an annual grassland with elevated carbon dioxide (CO 2 ), nitrate deposition, temperature, and precipitation – we used six indices of phosphorus (P) limitation to test the hypothesis that global changes that increase net primary production (NPP) increase P demand or limitation. All indices indicated that nitrate deposition, the only factor that stimulated NPP, increased P demand or limitation: (1) soil phosphatase activity increased by 14%; (2) P concentration in green and (3) senescent leaves of the dominant grass genus, Avena , dropped by 40% and 44%, respectively; (4) N : P ratios in green and (5) senescent Avena widened by 99% and 161%, respectively; and (6) total aboveground plant P decreased by 17% with elevated nitrate deposition. The other three factors, which did not stimulate NPP, did not increase P demand: based on two indices, enhanced precipitation decreased P demand (11% decrease in phosphatase activity, 19% increase in total aboveground P), and there was no evidence that elevated CO 2 or temperature altered P demand. In a meta‐analysis to assess the generality of P constraints on growth increases from global change factors, we found that six of 11 N‐limited ecosystems responded to N deposition with enhanced P limitation or demand, but did not detect significant effects of elevated CO 2 or warming.

Historical effects of temperature and precipitation on California crop yields - David B. Lobell; Kimberly Nicholas Cahill; Christopher B. Field (Climatic Change, 2007)

Interactive Effects of Fire, Elevated Carbon Dioxide, Nitrogen Deposition, and precipitation on a California Annual Grassland - Hugh A. L. Henry; Nona R. Chiariello; Peter M. Vitousek; Harold A. Mooney; Christopher B. Field (Ecosystems, 2006)

The effects of elevated atmospheric CO 2 on the amount and depth distribution of plant water uptake in a California annual grassland - LISA A. MOORE; CHRISTOPHER B. FIELD (Global Change Biology, 2006)
Soil moisture profiles can affect species composition and ecosystem processes, but the effects of increased concentrations of atmospheric carbon dioxide ([CO 2 ]) on the vertical distribution of plant water uptake have not been studied. Because plant species composition affects soil moisture profiles, and is likely to shift under elevated [CO 2 ], it is also important to test whether the indirect effects of [CO 2 ] on soil water content may depend on species composition. We examined the effects of elevated [CO 2 ] and species composition on soil moisture profiles in an annual grassland of California. We grew monocultures and a mixture of Avena barbata and Hemizonia congesta – the dominant species of two phenological groups – in microcosms exposed to ambient (∼370 μmol mol −1 ) and elevated (∼700 μmol mol −1 ) [CO 2 ]. Both species increased intrinsic and yield‐based water use efficiency under elevated [CO 2 ], but soil moisture increased only in communities with A . barbata , the dominant early‐season annual grass. In A. barbata monocultures, the [CO 2 ] treatment did not affect the depth distribution of soil water loss. In contrast to communities with A. barbata , monocultures of H. congesta , a late‐season annual forb, did not conserve water under elevated [CO 2 ], reflecting the increased growth of these plants. In late spring, elevated [CO 2 ] also increased the efficiency of deep roots in H. congesta monocultures. Under ambient [CO 2 ], roots below 60 cm accounted for 22% of total root biomass and were associated with 9% of total water loss, whereas in elevated [CO 2 ], 16% of total belowground biomass was associated with 34% of total water loss. Both soil moisture and isotope data showed that H. congesta monocultures grown under elevated [CO 2 ] began extracting water from deep soils 2 weeks earlier than plants in ambient [CO 2 ].

Herbivore control of annual grassland composition in current and future environments - Halton A. Peters; Elsa E. Cleland; Harold A. Mooney; Christopher B. Field (Ecology Letters, 2006)
Selective consumption by herbivores influences the composition and structure of a range of plant communities. Anthropogenically driven global environmental changes, including increased atmospheric carbon dioxide (CO 2 ), warming, increased precipitation, and increased N deposition, directly alter plant physiological properties, which may in turn modify herbivore consumption patterns. In this study, we tested the hypothesis that responses of annual grassland composition to global changes can be predicted exclusively from environmentally induced changes in the consumption patterns of a group of widespread herbivores, the terrestrial gastropods. This was done by: (1) assessing gastropod impacts on grassland composition under ambient conditions; (2) quantifying environmentally induced changes in gastropod feeding behaviour; (3) predicting how grassland composition would respond to global‐change manipulations if influenced only by herbivore consumption preferences; and (4) comparing these predictions to observed responses of grassland community composition to simulated global changes. Gastropod herbivores consume nearly half of aboveground production in this system. Global changes induced species‐specific changes in plant leaf characteristics, leading gastropods to alter the relative amounts of different plant types consumed. These changes in gastropod feeding preferences consistently explained global‐change‐induced responses of functional group abundance in an intact annual grassland exposed to simulated future environments. For four of the five global change scenarios, gastropod impacts explained > 50% of the quantitative changes, indicating that herbivore preferences can be a major driver of plant community responses to global changes.

Interactive effects of elevated CO 2 , N deposition and climate change on extracellular enzyme activity and soil density fractionation in a California annual grassland - Hugh A. L. Henry; John D. Juarez; Christopher B. Field; Peter M. Vitousek (Global Change Biology, 2005)
Elevated CO 2 , N deposition and climate change can alter ecosystem‐level nutrient cycling both directly and indirectly. We explored the interactive effects of these environmental changes on extracellular enzyme activity and organic matter fractionation in soils of a California annual grassland. The activities of hydrolases (polysaccharide‐degrading enzymes and phosphatase) increased significantly in response to nitrate addition, which coincided with an increase in soluble C concentrations under ambient CO 2 . Water addition and elevated CO 2 had negative but nonadditive effects on the activities of these enzymes. In contrast, water addition resulted in an increase in the activities of lignin‐degrading enzymes (phenol oxidase and peroxidase), and a decrease in the free light fraction (FLF) of soil organic matter. Independent of treatment effects, lignin content in the FLF was negatively correlated with the quantity of FLF across all samples. Lignin concentrations were lower in the aggregate‐occluded light fraction (OLF) than the FLF, and there was no correlation between percent lignin and OLF quantity, which was consistent with the protection of soil organic matter in aggregates. Elevated CO 2 decreased the quantity of OLF and increased the OLF lignin concentration, however, which is consistent with increased degradation resulting from increased turnover of soil aggregates. Overall, these results suggest that the effects of N addition on hydrolase activity are offset by the interactive effects of water addition and elevated CO 2 , whereas water and elevated CO 2 may cause an increase in the breakdown of soil organic matter as a result of their effects on lignin‐degrading enzymes and soil aggregation, respectively.

Fire history and the global carbon budget: a 1°× 1° fire history reconstruction for the 20th century - Florent Mouillot; Christopher B. Field (Global Change Biology, 2005)
A yearly global fire history is a prerequisite for quantifying the contribution of previous fires to the past and present global carbon budget. Vegetation fires can have both direct (combustion) and long‐term indirect effects on the carbon cycle. Every fire influences the ecosystem carbon budget for many years, as a consequence of internal reorganization, decomposition of dead biomass, and regrowth. We used a two‐step process to estimate these effects. First we synthesized the available data available for the 1980s or 1990s to produce a global fire map. For regions with no data, we developed estimates based on vegetation type and history. Second, we then worked backwards to reconstruct the fire history. This reconstruction was based on published data when available. Where it was not, we extrapolated from land use practices, qualitative reports and local studies, such as tree ring analysis. The resulting product is intended as a first approximation for questions about consequences of historical changes in fire for the global carbon budget. We estimate that an average of 608 Mha yr −1 burned (not including agricultural fires) at the end of the 20th century. 86% of this occurred in tropical savannas. Fires in forests with higher carbon stocks consumed 70.7 Mha yr −1 at the beginning of the century, mostly in the boreal and temperate forests of the Northern Hemisphere. This decreased to 15.2 Mha yr −1 in the 1960s as a consequence of fire suppression policies and the development of efficient fire fighting equipment. Since then, fires in temperate and boreal forests have decreased to 11.2 Mha yr −1 . At the same time, burned areas increased exponentially in tropical forests, reaching 54 Mha yr −1 in the 1990s, reflecting the use of fire in deforestation for expansion of agriculture. There is some evidence for an increase in area burned in temperate and boreal forests in the closing years of the 20th century.

Interactive effects of elevated CO2, N deposition and climate change on plant litter quality in a California annual grassland - Hugh A. L. Henry; Elsa E. Cleland; Christopher B. Field; Peter M. Vitousek (Oecologia, 2005)

Postfire response of North American boreal forest net primary productivity analyzed with satellite observations - Jeffrey A. Hicke; Gregory P. Asner; Eric S. Kasischke; Nancy H. F. French; James T. Randerson; G. James Collatz; Brian J. Stocks; Compton J. Tucker; Sietse O. Los; Christopher B. Field (Global Change Biology, 2003)
Fire is a major disturbance in the boreal forest, and has been shown to release significant amounts of carbon (C) to the atmosphere through combustion. However, less is known about the effects on ecosystems following fire, which include reduced productivity and changes in decomposition in the decade immediately following the disturbance. In this study, we assessed the impact of fire on net primary productivity (NPP) in the North American boreal forest using a 17‐year record of satellite NDVI observations at 8‐ km spatial resolution together with a light‐use efficiency model. We identified 61 fire scars in the satellite observations using digitized fire burn perimeters from a database of large fires. We studied the postfire response of NPP by analyzing the most impacted pixel within each burned area. NPP decreased in the year following the fire by 60–260 g C m −2 yr −1 (30–80%). By comparing pre‐ and postfire observations, we estimated a mean NPP recovery period for boreal forests of about 9 years, with substantial variability among fires. We incorporated this behavior into a carbon cycle model simulation to demonstrate these effects on net ecosystem production. The disturbance resulted in a release of C to the atmosphere during the first 8 years, followed by a small, but long‐lived, sink lasting 150 years. Postfire net emissions were three times as large as from a model run without changing NPP. However, only small differences in the C cycle occurred between runs after 8 years due to the rapid recovery of NPP. We conclude by discussing the effects of fire on the long‐term continental trends in satellite NDVI observed across boreal North America during the 1980s and 1990s.

Arbuscular mycorrhizae respond to plants exposed to elevated atmospheric CO2 as a function of soil depth - Matthias C. Rillig; Christopher B. Field (Plant and Soil, 2003)

Temporal evolution of the European forest sector carbon sink from 1950 to 1999 - Gert‐Jan Nabuurs; Mart‐Jan Schelhaas; Godefridus (frits) M. J. Mohren; Christopher B. Field (Global Change Biology, 2003)
Estimates of the role of the European terrestrial biosphere in the global carbon cycle still vary by a factor 10. This is due to differences in methods and assumptions employed, but also due to difference in reference periods of the studies. The magnitude of the sink varies between years because of inter‐annual variation of short‐term climate, but also due to long‐term trends in development of the vegetation and its management. For this purpose, we present the results of an application of a carbon bookkeeping model to the forest sector of the European forests from 1950 to 1999. The analysis includes the compartments trees, soils, and wood products. The model uses statistics on European (30 countries excl. CIS) stemwood volume increment, forest area change, fellings, wood products and their international trade, and natural disturbances, supplemented with conversion coefficients, soil parameters and information on management. An (almost uninterrupted) increasing sink (Net Biome Production) in the European forest sector was found, increasing from 0.03 Pg C year −1 in the 1950s to 0.14 Pg C year −1 in the 1990s (for resp. 132 million hectares and 140 million hectares of forest). The sink in the tree and the soil compartment were approximately of the same size until 1970. After the 1970s the size of the sink in the tree biomass increases quickly, causing the tree biomass to account for some two thirds of the total sink in the 1990s. The results as presented here have to be regarded with caution especially with regard to the early decades of the analysis and with regard to the soil compartment.

Root production and demography in a california annual grassland under elevated atmospheric carbon dioxide - Paul A. T. Higgins; Robert B. Jackson; Julia M. Des Rosiers; Christopher B. Field (Global Change Biology, 2002)
This study examined root production and turnover in a California grassland during the third year of a long‐term experiment with ambient (LO) and twice‐ambient atmospheric CO 2 (HI), using harvests, ingrowth cores, and minirhizotrons. Based on one‐time harvest data, root biomass was 32% greater in the HI treatment, comparable to the stimulation of aboveground production during the study year. However, the 30–70% increase in photosynthesis under elevated CO 2 for the dominant species in our system is considerably larger than the combined increase in above and belowground biomass. One possible explanation is, increased root turnover, which could be a sink for the additional fixed carbon. Cumulative root production in ingrowth cores from both treatments harvested at four dates was 2–3 times that in the single harvested cores, suggesting substantial root turnover within the growing season. Minirhizotron data confirmed this result, demonstrating that production and mortality occurred simultaneously through much of the season. As a result, cumulative root production was 54%, 47% and 44% greater than peak standing root length for the no chamber (X), LO, and HI plots, respectively. Elevated CO 2 , however, had little effect on rates of turnover (i.e. rates of turnover were equal in the LO and HI plots throughout most of the year) and cumulative root production was unaffected by treatment. Elevated CO 2 increased monthly production of new root length (59%) only at the end of the season (April–June) when root growth had largely ceased in the LO plots but continued in the HI plots. This end‐of‐season increase in production coincided with an 18% greater soil moisture content in the HI plots previously described. Total standing root length was not affected by CO 2 treatment. Root mortality was unaffected by elevated CO 2 in all months except April, in which plants grown in the HI plots had higher mortality rates. Together, these results demonstrate that root turnover is considerable in the grassland community and easily missed by destructive soil coring. However, increased fine root turnover under elevated CO 2 is apparently not a major sink for extra photosynthate in this system.

Tree Mortality in Gap Models: Application to Climate Change - Robert E. Keane; Mike Austin; Christopher Field; Andreas Huth; Manfred J. Lexer; Debra Peters; Allen Solomon; Peter Wyckoff (Climatic Change, 2001)

Species‐specific responses of plant communities to altered carbon and nutrient availability - Geeske Joel; F. Stuart Chapin; Nona R. Chiariello; Susan S. Thayer; Christopher B. Field (Global Change Biology, 2001)
Summary In a field microcosm experiment, species‐specific responses of aboveground biomass of two California annual grassland communities to elevated CO 2 and nutrient availability were investigated. One community grows on shallow, nutrient‐poor serpentine‐derived soil whereas the other occurs on deeper, modestly fertile sandstone/greenstone‐derived substrate. In most species, CO 2 effects did not appear until late in the growing season, probably because the elevated CO 2 increased water‐use‐efficiency easing, the onset of the summer drought. Responses of aboveground biomass to elevated CO 2 differed depending on nutrient availability. Similarly, biomass responses to nutrient treatments differed depending on the CO 2 status. For the majority of the species, production increased most under elevated CO 2 with added nutrients (N,P,K, and micro nutrients). Some species were losers under conditions that increased overall community production, including Bromus hordeaceus in the serpentine community (negative biomass response under elevated CO 2 ) and Lotus wrangelianus in both communities (negative biomass response with added nitrogen). Treatment and competitive effects on species‐specific biomass varied in both magnitude and direction, especially in the serpentine community, significantly affecting community structure. Individual resource environments are likely to be affected by neighbouring plants, and these competitive interactions complicate predictions of species' responses to elevated CO 2 .

Introduction - Joseph A. Berry; Christopher B. Field; Arthur R. Grossman (Photosynthesis Research, 2001)

Assessing photosynthetic downregulation in sunflower stands with an optically-based model - John A. Gamon; Christopher B. Field; Arthur L. Fredeen; Susan Thayer (Photosynthesis Research, 2001)

Diverse mechanisms for CO 2 effects on grassland litter decomposition - Jeffrey S. Dukes; Christopher B. Field (Global Change Biology, 2000)
Summary The ongoing increase in atmospheric CO 2 concentration ([CO 2 ]) can potentially alter litter decomposition rates by changing: (i) the litter quality of individual species, (ii) allocation patterns of individual species, (iii) the species composition of ecosystems (which could alter ecosystem‐level litter quality and allocation), (iv) patterns of soil moisture, and (v) the composition and size of microbial communities. To determine the relative importance of these mechanisms in a California annual grassland, we created four mixtures of litter that differed in species composition (the annual legume Lotus wrangelianus Fischer & C. Meyer comprised either 10% or 40% of the initial mass) and atmospheric [CO 2 ] during growth (ambient or double‐ambient). These mixtures decomposed for 33 weeks at three positions (above, on, and below the soil surface) in four types of grassland microcosms (fertilized and unfertilized microcosms exposed to elevated or ambient [CO 2 ]) and at a common field site. Initially, legume‐rich litter mixtures had higher nitrogen concentrations ([N]) than legume‐poor mixtures. In most positions and environments, the different litter mixtures decomposed at approximately the same rate. Fertilization and CO 2 enrichment of microcosms had no effect on mass loss of litter within them. However, mass loss was strongly related to litter position in both microcosms and the field. Nitrogen dynamics of litter were significantly related to the initial [N] of litter on the soil surface, but not in other positions. We conclude that changes in allocation patterns and species composition are likely to be the dominant mechanisms through which ecosystem‐level decomposition rates respond to increasing atmospheric [CO 2 ].

Soil biota responses to long-term atmospheric CO 2 enrichment in two California annual grasslands - Matthias C. Rillig; Christopher B. Field; Michael F. Allen (Oecologia, 1999)

Fungal root colonization responses in natural grasslands after long‐term exposure to elevated atmospheric CO 2 - Matthias C. Rillig; Christopher B. Field; Michael F. Allen (Global Change Biology, 1999)
Summary Arbuscular mycorrhizae, ubiquitous mutualistic symbioses between plant roots and fungi in the order Glomales , are believed to be important controllers of plant responses to global change, in particular to elevated atmospheric CO 2 . In order to test if any effects on the symbiosis can persist after long‐term treatment, we examined root colonization by arbuscular mycorrhizal (AM) and other fungi of several plant species from two grassland communities after continuous exposure to elevated atmospheric CO 2 for six growing seasons in the field. For plant species from both a sandstone and a serpentine annual grassland there was evidence for changes in fungal root colonization, with changes occurring as a function of plant host species. We documented decreases in percentage nonmycorrhizal fungal root colonization in elevated CO 2 for several plant species. Total AM root colonization (%) only increased significantly for one out of the five plant species in each grassland. However, when dividing AM fungal hyphae into two groups of hyphae (fine endophyte and coarse endophyte), we could document significant responses of AM fungi that were hidden when only total percentage colonization was measured. We also documented changes in elevated CO 2 in the percentage of root colonized by both AM hyphal types simultaneously. Our results demonstrate that changes in fungal root colonization can occur after long‐term CO 2 enrichment, and that the level of resolution of the study of AM fungal responses may have to be increased to uncover significant changes to the CO 2 treatment. This study is also one of the first to document compositional changes in the AM fungi colonizing roots of plants grown in elevated CO 2 . Although it is difficult to relate the structural data directly to functional changes, possible implications of the observed changes for plant communities are discussed.

The photosynthesis – leaf nitrogen relationship at ambient and elevated atmospheric carbon dioxide: a meta‐analysis - Andrew G. Peterson; J. Timothy Ball; YiqI. Luo; Christopher B. Field; Peter B. Reich; Peter S. Curtis; Kevin L. Griffin; Carla A. Gunderson; Richard J. Norby; David T. Tissue; Manfred Forstreuter; AnA. Rey; et al. (Global Change Biology, 1999)
Estimation of leaf photosynthetic rate ( A ) from leaf nitrogen content ( N ) is both conceptually and numerically important in models of plant, ecosystem, and biosphere responses to global change. The relationship between A and N has been studied extensively at ambient CO 2 but much less at elevated CO 2 . This study was designed to (i) assess whether the A–N relationship was more similar for species within than between community and vegetation types, and (ii) examine how growth at elevated CO 2 affects the A–N relationship. Data were obtained for 39 C3 species grown at ambient CO 2 and 10 C3 species grown at ambient and elevated CO 2 . A regression model was applied to each species as well as to species pooled within different community and vegetation types. Cluster analysis of the regression coefficients indicated that species measured at ambient CO 2 did not separate into distinct groups matching community or vegetation type. Instead, most community and vegetation types shared the same general parameter space for regression coefficients. Growth at elevated CO 2 increased photosynthetic nitrogen use efficiency for pines and deciduous trees. When species were pooled by vegetation type, the A–N relationship for deciduous trees expressed on a leaf‐mass basis was not altered by elevated CO 2 , while the intercept increased for pines. When regression coefficients were averaged to give mean responses for different vegetation types, elevated CO 2 increased the intercept and the slope for deciduous trees but increased only the intercept for pines. There were no statistical differences between the pines and deciduous trees for the effect of CO 2 . Generalizations about the effect of elevated CO 2 on the A–N relationship, and differences between pines and deciduous trees will be enhanced as more data become available.

Bidirectional Interactions between the Biosphere and the Atmosphere—introduction - Christopher B. Field; RonI. Avissar (Global Change Biology, 1998)

Bidirectional Interactions between the Biosphere and the Atmosphere—introduction - CHRISTOPHER B. FIELD; RONI AVISSAR (Global Change Biology, 1998)

Plant species-specific changes in root-inhabiting fungi in a California annual grassland: responses to elevated CO 2 and nutrients - Matthias C. Rillig; Michael F. Allen; John N. Klironomos; Nona R. Chiariello; Christopher B. Field (Oecologia, 1998)

CO 2 effects on the water budget of grassland microcosm communities - CHRISTOPHER FIELD; CHRISTOPHER LUND; NONA CHIARIELLO; BARBARA MORTIMER (Global Change Biology, 1997)
Experimental grassland ecosystems, in microcosms 0.2 m in diameter and with a 0.95 m soil column, varied in their responses to elevated partial pressure of CO 2 (pCO 2 ) and altered moisture inputs. Ecosystems on moderately fertile sandstone soil and with a typical mix of moderately fast‐growing sandstone species, responded to elevated pCO 2 with decreases in mid‐season evapotranspiration of nearly 50%. This pattern reversed at the end of the growing season, and sandstone ecosystems under elevated pCO 2 continued active transpiration farther into the summer drought. The sandstone ecosystems appeared to convert mid‐season water conservation into increased late‐season growth. Effects of increased pCO 2 on ecosystem evapotranspiration were much smaller in ecosystems with very infertile serpentine soil and a diverse mixture of slow‐growing serpentine species.